Pengaruh Kompetensi Profesional Guru Terhadap Hasil Belajar Siswa Pada Mata Pelajaran IPS di SMP Satap Negeri Mataindo Kabupaten Bolaang Mongondow Selatan - Fahira Basir; Agil Bahsoan; Abdulrahim Maruwae; Meyko Panigoro; Sudirman Sudirman (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2026)
This study aimed to determine the influence of teachers' professional competence on students' learning outcomes in Social Studies subjects at SMP Satap Mataindo. The background of this study was the relatively low student learning outcomes that had not yet met the Minimum Completeness Criteria (KKM), as well as the important role of teachers as a primary factor in the success of the learning process. The study's findings indicated that teachers' professional competence was high, with an average score of 4.40. In addition, the regression analysis showed a positive and significant influence of teachers' professional competence on students' learning outcomes, with the regression equation Y = 20,440 +0.629. This means that every improvement in teachers' professional competence is followed by an increase in students' learning outcomes.